THE FEAR ENDEMIC OF COVID-19: MYTHS, CONSPIRACY THEORIES AND CYBERCRIME IN THE CORONAVIRUS MULTIVERSE (Proceedings of the International Conference on Education, 2023)
The COVID-19 pandemic signals the age that digital technologies have come to dominate our realities and create their own, based on fear, insecurities and anxieties. Hyperspace has emerged as the main area of contesting and negotiating truth and reality. During the pandemic months dangerous trends set off online involving, the dissemination of myths and misinformation, the rise of conspiracy theories and the increase of cybercrime activities. The current paper looks these digital hyperrealities circulated during the first months of the COVID-19 pandemic to provide a deeper understanding, a wider awareness and an increased vigilance to protect from these threats. Above all, the COVID-19 pandemic has shown the power of information to form opinions, beliefs, attitudes and behaviors that have an impact on the life in the physical world. It also exposed the questionable operation of media disseminated information and the consequent produced knowledge by those who own, those who exploit, and those who thrive on, the digital technologies landscape worldwide.
Keywords: COVID-19; cybercrime; conspiracy theories; misinformation; digital technologies